Investigation of Elemental Deposition in Lamdong Province (Vietnam) by the Moss Biomonitoring Method and Neutron Activation Analysis - Nguyen, Thi Minh Sang; Nguyen, Anh Son; Khiem, Le Hong; Le, Thi Thanh Tran; Tran, Tuan Anh; Ho, Huu Thang; Zinicovscaia, Inga; Frontasyeva, Marina; Le, Dai Nam; Nguyen, Thi Xuan Thai (Communications in Physics, 2023)
The results of an investigation of heavy metal air pollution in Lamdong province (Vietnam) using the moss biomonitoring method are presented in this paper. Barbula Indica moss samples were collected at 30 different locations in Dalat and Baoloc, two major cities of Lamdong province. The concentrations of 10 heavy metal and metalloid elements, Sc, V, Cr, Mn, Fe, Co, Zn, As, Hf, and Ta in the collected moss samples, were determined by the neutron activation analysis method using the nuclear reactor at the Nuclear Research Institute in Dalat. The results show that the air in Lamdong province may be polluted by Mn and is moderately polluted by Sc, V, Cr, Fe, Co, Zn, As, Hf and Ta. The main sources of heavy metal pollution in the Lamdong atmosphere may be soil dust, traffic emissions, industry, bauxite mining and refining, chemical fertilizers and pesticides, and combustion of coal and oil. By comparing heavy element concentrations in the moss from Lamdong with that of Hanoi, Thainguyen, and several European countries, it is found that heavy metal air pollution in Lamdong is much lower than in Hanoi and Thainguyen and much higher than in the European countries.